4x-3y=-9

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 4x from both sides of the equation.

-3y=-9-4x

Divide each term by -3 and simplify.

Divide each term in -3y=-9-4x by -3.

-3y-3=-9-3+-4x-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=-9-3+-4x-3

Divide y by 1.

y=-9-3+-4x-3

y=-9-3+-4x-3

Simplify -9-3+-4x-3.

Simplify each term.

Divide -9 by -3.

y=3+-4x-3

Dividing two negative values results in a positive value.

y=3+4×3

y=3+4×3

Reorder 3 and 4×3.

y=4×3+3

y=4×3+3

y=4×3+3

Rewrite in slope-intercept form.

y=43x+3

y=43x+3

Rewrite in Slope-Intercept Form 4x-3y=-9